2014
DOI: 10.1002/glia.22678
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal release and successful astrocyte uptake of aminoacidergic neurotransmitters after spinal cord injury in lampreys

Abstract: In contrast to mammals, the spinal cord of lampreys spontaneously recovers from a complete spinal cord injury (SCI). Understanding the differences between lampreys and mammals in their response to SCI could provide valuable information to propose new therapies. Unique properties of the astrocytes of lampreys probably contribute to the success of spinal cord regeneration. The main aim of our study was to investigate, in the sea lamprey, the release of aminoacidergic neurotransmitters and the subsequent astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 82 publications
6
31
0
Order By: Relevance
“…This is in agreement with our previous results in which we have reported a complete disappearance of glutamate immunoreactivity in region 2 of the spinal cord immediately after a SCI25. This is followed by a gradual increase until 4 to 10 wpl, when the number of glutamate-ir cells is slightly higher than that of control un-lesioned animals (between 1.2 to1.5 times higher).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is in agreement with our previous results in which we have reported a complete disappearance of glutamate immunoreactivity in region 2 of the spinal cord immediately after a SCI25. This is followed by a gradual increase until 4 to 10 wpl, when the number of glutamate-ir cells is slightly higher than that of control un-lesioned animals (between 1.2 to1.5 times higher).…”
Section: Discussionsupporting
confidence: 93%
“…In a recent study in lampreys, we found a complete disappearance of glutamate immunoreactivity immediately after a complete transection of the cord rostrally and caudally to the site of injury25, which was related to excessive glutamate release. Based on these previous results, the main aims of the present study were (1) to determine whether, in lampreys, axotomized glutamatergic neurons that lose glutamate immunoreactivity immediately after SCI are able to recover it later on, evaluating the possible contribution of cell death to this initial loss of glutamate immunoreactivity and (2) to study the long-term evolution of the glutamatergic system (cells and fibres) after a complete SCI in lampreys.…”
mentioning
confidence: 63%
See 3 more Smart Citations